2005
DOI: 10.1038/nature04132
|View full text |Cite
|
Sign up to set email alerts
|

Force production by disassembling microtubules

Abstract: Microtubules (MTs) are important components of the eukaryotic cytoskeleton: they contribute to cell shape and movement, as well as to the motions of organelles including mitotic chromosomes. MTs bind motor enzymes that drive many such movements, but MT dynamics can also contribute to organelle motility. Each MT polymer is a store of chemical energy that can be used to do mechanical work, but how this energy is converted to motility remains unknown. Here we show, by conjugating glass microbeads to tubulin polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
249
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(258 citation statements)
references
References 30 publications
6
249
1
2
Order By: Relevance
“…Indeed, microtubule depolymerization can generate a force 10 times greater than that of a microtubule motor protein. 123 The force of microtubule plus-end depolymerization has a crucial role in generating the tension that pulls a chromatid from its sister. [124][125][126] In fact, in fission yeast, minus end-directed motor proteins are entirely dispensable for poleward motion of chromosomes -the force generated by microtubule depolymerization is sufficient.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 99%
“…Indeed, microtubule depolymerization can generate a force 10 times greater than that of a microtubule motor protein. 123 The force of microtubule plus-end depolymerization has a crucial role in generating the tension that pulls a chromatid from its sister. [124][125][126] In fact, in fission yeast, minus end-directed motor proteins are entirely dispensable for poleward motion of chromosomes -the force generated by microtubule depolymerization is sufficient.…”
Section: Surviving With Surplus: Managing Supernumerary Centrosomes Bmentioning
confidence: 99%
“…Our findings help establish the benchmark parameters of the Dam1 coupler and elucidate the mechanism of its functions. Dam1 | microtubule | kinetochore D uring mitotic chromosome segregation, sister chromatids are tightly attached to spindle MTs, and their migration is powered by MT depolymerization as well as specific motor proteins (1). The kinetochore (k), a mega-protein complex assembled on the centromere of each chromosome, mediates the association between the chromosome and the kMTs, and is responsible for generating the pulling forces for chromosome motions (2).…”
mentioning
confidence: 99%
“…Accordingly, it was determined that the maximal force generated was ~46 pN, which might correspond to the bending of 1 or 2 protofilaments. This is about 10 times the force developed by kinesin molecules [137] and it is expected that at kinetochores, with a proper coupler, all protofilaments would act in concert, increasing the force generated by a depolymerizing microtubule to at least 30-65 pN [136]. In agreement, the force produced by this system was shown to be dependent on the curvature of protofilaments [138].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 61%
“…In 2005, McIntosh and co-workers provided theoretical and experimental evidence in support of the conformational-wave model [135,136]. By conjugating streptavidin coated glass microbeads to biotinylated microtubules they observed that upon depolymerization, microtubules exert a brief pull on the beads before being released.…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%